Requirements in Earth Science Teacher Preparation Programs: 1965 To 1974. - Mayer, Victor J. (Science Education)
The article assesses the status of the college and university programs specifically designed for the preservice preparation of earth science teachers in the U.S. from 1965-1974. the author contends that the surveys provides an opportunity to document changes in one particular area of teacher preparation, but also permits some conclusions regarding the ability of higher educational institutions to respond to needs for new programs and to recommendations for revision of existing programs. The examination of the breadth requirements in the earth sciences indicated an increase in programs requiring oceanography and a decrease in those requiring physical geography. The criterion model used in the study reflects an emphasis upon interdisciplinary approaches to organizing instruction in earth science.